Simultaneously focusing electromagnetic and acoustic waves by double-physical-fields null medium - Wu, Boyang; Sun, Fei; Liu, Yichao; Liu, Xin; Zhao, Xiaodan; Fei, Hongming; Yang, Yibiao; Chen, Zhihui; Liang, Shaowei; Wang, Zheng; Wang, Bingjie (Frontiers in Materials, 2023)
A novel double-physical-fields lens that can simultaneously focus acoustic and electromagnetic waves into a given region is designed based on double-physical-fields null medium, which can be realized by metal plates with subwavelength separations/thicknesses and precisely designed lengths. Numerical simulations show the proposed double-physical-fields lens can create exactly the same focusing effect for both electromagnetic and acoustic waves, i.e., the same focal spot size and efficiency at the same focal length. Four typical lens with different output surfaces are studied, which shows different focusing characteristics, e.g., noodle-shaped focal spot, tiny focal spot, and capsule-shaped focal spot. With the help of the designed double-physical-fields lens, an additional degree of freedom for control can be provided by simultaneously focusing acoustic and electromagnetic waves, which may lead to wider range of applications than single-field focusing.